KUALITAS PELAYANAN PENERBITAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PALU - Nelvianti, Nelvianti (Katalogis, 2015)
The purpose of this study was to find out how the quality of birth certificates issuance service at Palu City Population and Civil Registry. Types of data used were primary and secondary data. Data collection was done by means of observations, interviews, documentations. Informant determination technique was purposive sampling for the employees and accidental sampling for the community. Informants in this study were amounting to five (5) people. Analysis of data used was Miles and Huberman model, namely data reduction, data presentation, and conclusion. The theory used was the theory of Parasuraman in Tangkilisan. Birth certificate issuance service quality at the Office of Palu City Population and Civil Registry was still not good. It was known from the five aspects which were used as parameters in this study, namely direct evidence (tangibles): facility and infrastructure was inadequate and the employees appearance was not fully neat; reliability: the service provided was less precise and fast; responsiveness: the employees response was less fast enough to serve the needs or concerns of the community, assurance: there were still lacks of politeness and friendliness from the employees in serving the community; and empaty: there was a less fair service in serving the community.